Comparison of time to negative conversion of SARS-CoV-2 between young and elderly among asymptomatic and mild COVID-19 patients: a cohort study from a national containment center - Zemni, Imen; Bennasrallah, Cyrine; Charrada, Ines; Dhouib, Wafa; Maatouk, Amani; Hassine, Donia Ben; Klii, Rim; Kacem, Meriem; Fredj, Manel Ben; Abroug, Hela; Mhalla, Salma; Mastouri, Maha; et al. (Frontiers in Medicine, 2024)
Objective We aimed to study the relationship between age and time to negative conversion of SARS-CoV-2 in patients with asymptomatic and mild forms of COVID-19. Methods We conducted a cohort study including all patients diagnosed with COVID-19 from the national COVID-19 containment center of Tunisia. Patients were subdivided into two cohorts: (under 60 years) and (over 60 years) and were followed up until PCR negativization. Log rank test and Cox regression were applied to compare time to negative conversion between the old group and the young group. Results The study included 289 patients with non-severe forms of COVID-19. Age over 60 was significantly associated with delayed negative conversion in male sex (Hazard ratio (HR): 1.9; 95% CI: 1.2–3.07) and among patients with morbid conditions (HR:1.68; 95% CI: 1.02–2.75) especially diabetics (HR: 2.06; 95% CI: 1.01–4.21). This association increased to (HR:2.3; 95% CI: 1.13–4.66) when male sex and comorbidities were concomitantly present and rose to (HR: 2.63; 95% CI: 1.02–6.80) for men with diabetes. Cox regression analysis revealed a significantly delayed negative conversion in symptomatic patients. Significant interaction was observed between gender and age and between age and chronic conditions. Conclusion Age is associated with delayed negative conversion of viral RNA in certain subgroups. Identifying these subgroups is crucial to know how prioritize preventive strategies in elderly.